Art Making Promotes Mental Health: A Solution for Schools That Time Forgot - Martin, Brittany Harker; Colp, S. Mitchell (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
This article presents art as a tool for promoting mental health in schools by examining the effects of art making in a sample of 104 school-based mental health professionals. It unites findings from unrelated disciplines to derive and test a new conceptual framework proposing that active engagement in a visual-tactile process over time mediates a shift to healthy mental states and that regular engagement in such process builds mental health capacity. Four hypotheses are tested through psychometrics with statistically significant findings for all (p < .05). Through this study, we advance Flow Theory in identifying a new causal mechanism for accessing Flow; and we make a novel, interdisciplinary contribution to the field of mental health in providing psychometric evidence that making visual art promotes mental health.